Pengaruh Model Pembelajaran dan Kemampuan Siswa Memanfaatkan TIK terhadap Hasil Belajar Bahasa Indonesia - Khaerunnisa - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
he aim of this research was to nd the effect of learning models and student’s ICT competence on the learning outcomes of indonesian languge. The research was conducted at the SMK Negeri 17 Jakarta involving samples of 36 students that selected randomly. The result of the study was analyzed with two-way analysis of variance (ANOVA) and followed by Tukey’s test. The results indicate: (1) learning outcomes of the students group using CTL model is higher than expository model; (2) there is an interraction effect of learning model and students’ ICT competence; (3) contextual model brings higher learning outcomes of bahasa to the students group of higher ICT competence; (4) expository model brings higher learning outcomes of bahasa to the students group of lower ICT competence.